The Question of Hawks in Iowa - DuMont, Philip A. (Philip Atkinson), 1903-1996 (2017)
Draft article. In this article Philip DuMont responds to the question whether Hawks are as destructive as many people believe. Published in Iowa Game Birds, vol. 1, no. 3.